2015
DOI: 10.1016/j.apcata.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of H2S, SO2, and COS poisoning on Ni/YSZ and Ni/K2O-CaAl2O4 during methane steam and dry reforming

Abstract: Research Highlights: The impact of sulfur poisoning by H 2 S, SO 2 , and COS on methane steam and dry reforming over Ni/YSZ and Ni/K 2 O-CaAl 2 O 4 was measured. Ni/YSZ has 15 times lower active nickel surface area than Ni/K 2 O-CaAl 2 O 4 as measured by hydrogen uptake. Ni/YSZ is essentially completely deactivated while Ni/K 2 O-CaAl 2 O 4 maintains some activity for the same time on stream. For both catalysts, the deactivation rates by H 2 S and SO 2 are comparable, while that for COS is much higher. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…As has been reported by other authors, the deactivation by sulfur can be described by the following general reaction Equation (8) [32,33], which is proposed to operate at high temperature:…”
Section: Catalystsmentioning
confidence: 86%
“…As has been reported by other authors, the deactivation by sulfur can be described by the following general reaction Equation (8) [32,33], which is proposed to operate at high temperature:…”
Section: Catalystsmentioning
confidence: 86%
“…Typical concentrations of sulfur impurity are in the range of 5–500 ppm for natural gas and 200–20,000 ppm for biogas . Experiments have shown that the tolerance of Ni‐based anode is below 5 ppm H 2 S at 950–1000°C .…”
Section: Resultsmentioning
confidence: 99%
“…bold-italicpbold-italicH2bold-italicSbold-italics and bold-italicpbold-italicH2bold-italics are the partial pressures of H 2 S and H 2 in the activation layer. pH2 and pH2S are calculated through the Hertz‐Knudsen equation with the sticking probability, γ, pH2=A1rnormalΓ22πMH2RTγH2onormalexp|E1rRT×104true[normalPnormalatrue] pH2S=A2rTβnormalΓ2πMH2SRTγH2Sonormalenormalxnormalptrue(E2rRTtrue)×104 true[normalPnormalatrue] where γH2So is the sticking probability and MH2…”
Section: Introductionmentioning
confidence: 99%
“…Sulfur reactivity with other metal catalysts is generally ordered as Ni [52] . Sulfur poisoning can be severe, meaning very low levels (e.g., ≤ 1 ppm) can severely reduce the catalytic activity [53][54][55] . Because sulfur is prevalent in petroleumand bio-derived fuels, understanding and controlling sulfur-catalyst interactions is important.…”
Section: Other Catalyst Degradation Mechanismsmentioning
confidence: 99%